G170(P) Subacute sclerosing panencephalitis (SSPE) a rare and fatal condition resulting from measles – report of three recent cases diagnosed in the UK. (May 2019) - Lam, T; Newark, K; Ranjan, R; Kaminska, M; Lim, M; Childs, AM; Gibbon, F; Thomas, G
Abstract : Objective: To report diagnostic and management challenges of SSPE. Methods: We present three 5-year-old children, diagnosed with SSPE in 2017/2018. All were UK citizens, though one had lived in Pakistan. All three children had been previously well, with normal development. The clinical features varied between cases. Early symptoms included mood lability, ataxia, loss of reading and writing skills, drop attacks and focal seizures. Progressive decline followed, and manifested in loss of speech and swallow, myoclonic jerks followed by hypertonic quadriplegia and in one case hemiplegia. The neurological decline was rapid in all cases, over a period between two and nine months. All cases presented a diagnostic challenge. The three children had followed childhood vaccination schedules. There was no clear history of measles in two at the time of presentation and in the case where there had been, initial CSF measles antibodies were negative. On further historical review, another had history of fever and an erythematous rash in infancy. There were recognised outbreaks of measles in two of the three local areas. Serial MRIs were normal in all three cases, until decline to stage four occurred, whereby MRI demonstrated global cerebral atrophy. Only in once case was the EEG pathognomonic for SSPE, when tested in the myoclonic stage. NMDAR antibodies were present in CSF in one of the two cases tested. Treatment varied between ribavirin and IVIG monthly infusions, isoprinosine and IVIG monthly infusions and palliative management. Conclusion: SSPE continues to present in young children in the UK and abroad, with particular vulnerability in unvaccinated infants. SSPE needs to be considered in acute neurological decline. We propose testing of SSPE cases for NMDAR antibodies. The role of NMDARE in SSPE needs to be evaluated carefully as may potentially confound the neurological symptoms with different treatment implications.